2011
DOI: 10.1111/j.1467-8500.2011.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Employee Motivation to Innovate: Evidence from Front Line Employees in United States Federal Agencies

Abstract: In a period of ongoing public sector reform in the United States (US), federal government agencies have been pushed to find new ways of performing their public functions more effectively and efficiently. Frontline public sector employees are a particularly vital source of innovations in organisational function and form. This study seeks to identify factors that motivate front line employees in the US federal bureaucracy to engage in innovative behaviour. The empirical analysis is based on data from the 2006 Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 72 publications
5
66
0
2
Order By: Relevance
“…This view was supported by Fernandez and Pitts (2011) who suggested that empowerment and employees' involvement in decision-making processes is one of the pivotal factors that may spur bottom-up innovation in public sector organisations. However, in this study the survey data reports that many public sector respondents (75% in Sicily, 42% in Portugal, 33% in Bulgaria) are not encouraged to look for new opportunities, nor are they empowered in the decision-making process within their organisations (75% in Sicily, 47% in Greece, 33% in Bulgaria).…”
Section: Organisations' Eo Empowerment and Encouragementmentioning
confidence: 97%
See 1 more Smart Citation
“…This view was supported by Fernandez and Pitts (2011) who suggested that empowerment and employees' involvement in decision-making processes is one of the pivotal factors that may spur bottom-up innovation in public sector organisations. However, in this study the survey data reports that many public sector respondents (75% in Sicily, 42% in Portugal, 33% in Bulgaria) are not encouraged to look for new opportunities, nor are they empowered in the decision-making process within their organisations (75% in Sicily, 47% in Greece, 33% in Bulgaria).…”
Section: Organisations' Eo Empowerment and Encouragementmentioning
confidence: 97%
“…According to Kuratko, Hornsby and Covin (2014) and Fernandez and Pitts (2011), one of the important drivers of employees' innovative behaviour is empowerment and perceived job autonomy that not only creates feelings of safety but also spurs the motivational state needed for generating creative solutions (and therefore improvements) at work. However, this study indicates that empowerment at lower grades (roles) may not necessarily impede one's ability to instigate different improvements at work.…”
Section: Organisations' Eo Empowerment and Encouragementmentioning
confidence: 99%
“…With respect to active system‐oriented coping, we expect that work autonomy increases learning behaviour as it creates the discretion people need in order to work towards new solutions (Hammond et al , p. 93) and motivates them to do so (Fernandez and Pitts ). Therefore, we expect work autonomy to increase the capacity and inclination of frontline employees to active system‐oriented coping.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…While some have written on the “motivation to innovate” (e.g., Perry et al, 1992; Fernandez and Pitts, 2011), there is no existing direct measure of intrapreneurial motivation in the social scientific literature. For the purpose of this study, we decided to develop a self-report measure of employee intrapreneurial motivation with reference to both Antoncic and Hisrich (2001) and de Jong and Den Hartog’s (2010) dimensions.…”
Section: Introductionmentioning
confidence: 99%